2023
DOI: 10.1177/09544062231187709
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study to determine proper steam-to-fuel ratio in a biogas-fueled solid oxide fuel cell for different levels of biogas methane content

Abstract: It is vital to find the optimal quantity of water added to the fuel in a biogas-fueled Solid Oxide Fuel Cell (SOFC). An under-optimal water quantity can impede steam reforming reactions, while an over-optimal quantity of water (which is equivalent to reduced biogas portion) may reduce the performance of the fuel cell due to a shortage of fuel. Water production in electrochemical reactions and the carbon deposition constraint add to the complexity of water quantity optimization. The present work develops a 3D n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…Thanks to these features, SOFCs provide fuel flexibility in energy production, effectively utilizing various fuel sources such as hydrogen, biogas, and methane. Experimental and numerical studies on the use of hydrocarbon-based fuels in SOFCs are documented in the literature [7][8][9][10][11][12][13]. Rath et al conducted a performance analysis of an anode-supported SOFC under various operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Thanks to these features, SOFCs provide fuel flexibility in energy production, effectively utilizing various fuel sources such as hydrogen, biogas, and methane. Experimental and numerical studies on the use of hydrocarbon-based fuels in SOFCs are documented in the literature [7][8][9][10][11][12][13]. Rath et al conducted a performance analysis of an anode-supported SOFC under various operating conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are several studies that have been carried out using the additional ANSYS Fluent SOFC module [14][15][16][17]. In this module, the electrolyte is represented as a pair of imaginary walls, called the "electrolyte surface," through which the movement of ions and electrons is simulated.…”
Section: Introductionmentioning
confidence: 99%
“…When analyzing publication activity from 2021 to 2024, it was revealed that the interest of researchers modeling SOFCs is aimed at studying the operation of a fuel cell using various types of organic and inorganic fuels, biofuels, and various agricultural and industrial wastes [12,14,16,27,38,39].…”
Section: Introductionmentioning
confidence: 99%